2020
DOI: 10.1002/pc.25752
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical research of temperature on tensile properties of multiaxial warp‐knitted composites

Abstract: A study on tensile behavior of composites reinforced with triaxial and quadriaxial warp-knitted glass fabrics were carried out in 0 , 45 , and 90 directions at temperature of −30 C, 0 C, 20 C, and 40 C. The stress-strain character, normalized strength, normalized modulus, failure strain, and the relationships between strength and temperature were also obtained. The failure mechanism was also analyzed based on the fracture mode and scanning electron microscopy morphology of composites. In addition, to obtain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As previously mentioned, the crack length a can be obtained for a known load P and an open displacement δ by using Equation (10). Thus, for a given load and the corresponding displacement, the crack length can be calculated using Equation (10). In addition, the crack length can also be measured from the crack propagation gage during the experiment.…”
Section: Calculation Of Crack Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the crack length a can be obtained for a known load P and an open displacement δ by using Equation (10). Thus, for a given load and the corresponding displacement, the crack length can be calculated using Equation (10). In addition, the crack length can also be measured from the crack propagation gage during the experiment.…”
Section: Calculation Of Crack Lengthmentioning
confidence: 99%
“…This obvious consideration points out that it is important to evaluate the delamination resistance of these materials not only in standard laboratory conditions but also under the conditions of more extreme environments. [9,10] Therefore, it is necessary to gain a comprehensive understanding of the interlaminar fracture toughness of the composite laminate when exposed to a broad range of temperatures. [11,12] Some studies have demonstrated how temperature influenced the delamination response of fiber-reinforced composite materials under different stress modes.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum process parameters for different 3D woven structural matrix composites were determined, and the optimum conditions were 12% hardener, 140°C curing temperature, 900 s curing time and 12 bar moulding pressure. Gao et al 18 investigated the tensile conduct of multi-axial warp-knitted composites who analyzed the impact of temperature on tensile conduct and injury mechanisms. The tensile strength decreases with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%